A Power Asymmetry – goodness of fit analysis of the agricultural outcome of Romania’s accession negotiations to the European Union - Irina Râmniceanu (Romanian Journal of European Affairs)
Starting from the power asymmetry concept, this paper aims to qualitatively assess the goodness of fit of the final agricultural package to the Romanian objective needs and possibilities. The power asymmetry will be linked to the common agricultural setup that the EU designed for all the newcomers, Romania included, but also to the differences between Romania’s initial position paper and the final outcome of the negotiations. The goodness of fit judgment implies reference to Romania’s output and structure as well as to its experience with Community compatible measures and institutional systems. For this purpose, the paper will focus (1) on some quantitative aspects of the negotiations (levels of single area payments and of reference areas or quantities) as well as (2) on the challenging aspects deriving from the adoption of particular parts of the relevant acquis communautaire (rural development regulations and cross-compliance).